Pengaruh Aksesibilitas Teknologi Informasi terhadap Pengetahuan tentang Diabetes Mellitus pada Mahasiswa Politeknik Piksi Ganesha - Maranata; Cyntia Rivatunisa; Karina Wahyu Noviyanti; Romia (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Diabetes is a chronic disease that occurs when blood sugar levels increase excessively. This disease can cause serious complications in many body systems, especially the nerves and blood vessels. Diabetes was the third highest cause of death in Indonesia in 2019, with around 57.42 deaths per 100,000 population. This study aims to explore the relationship between accessibility of information technology and knowledge of DM among students of Politeknik Piksi Ganesha. This study is a quantitative descriptive study with a cross-sectional approach, with a sample of 96 Politeknik Piksi Ganesha students selected using the purposive sampling method, analyzed using the Fisher's Exact test. Based on the results of the analysis, it was found that students' accessibility to television and radio had a significant effect on knowledge of diabetes mellitus (p 0.05). Although all students have accessibility to the internet and social media, not all of them have good knowledge of diabetes mellitus. Efforts to increase the knowledge of diabetes sufferers can be done by providing health education using various appropriate and interactive educational media